Role of civil society in economic transformation in Malaysia - Muhammad Jawad Iqbal; Amran Mohammed Rasli (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Malaysia is facing hurdles in knowledge economy transformation. To discover the knowledge based transformation solution, a quantitative, descriptive research design was used in which twenty nine economic performance determinant variables were tested for mediation with public/civil society. Two hundred and eighty two questionnaires were distributed to collect the data. The study validated the public/civil society mediation using regression analysis. Mediation was further validated using the Sobel Test. The study confirmed that the performance determinant variables have a strong and positive role in determining economy competitiveness. The results also confirm that strong civil society mediation is necessary; which is missing in Malaysia's economy. It is therefore, concluded that for successful knowledge based transformation, role of civil society sector is vital. It is thus recommended that a strong civil society supported innovation should be the focus and tool for knowledge based economic transformation to strengthen the economic performance and competitiveness of Malaysia.
Keywords: 330; transformation; knowledge economy; civil society; economic performance; competitiveness